2019
DOI: 10.1111/1365-2656.12942
|View full text |Cite
|
Sign up to set email alerts
|

The influence of symbiotic bacteria on reproductive strategies and wing polyphenism in pea aphids responding to stress

Abstract: 1. Environmental stressors can be key drivers of phenotypes, including reproductive strategies and morphological traits. The response to stress may be altered by the presence of microbial associates. For example, in aphids, facultative (secondary) bacterial symbionts can provide protection against natural enemies and stress induced by elevated temperatures. Furthermore, aphids exhibit phenotypic plasticity, producing winged (rather than wingless) progeny that may be better able to escape danger, and the combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…10 genotypes produced a low percentage of winged-offspring after crowding (weakly inducible genotypes: genotypes 73, 88, 183, 218, 223, 248, 375, 396, 405, & 495), and 10 genotypes produced a high percentage of winged-offspring (highly inducible genotypes: genotypes 42, 125, 179, 202, 217, 281, 286, 445, 473, & 500). We specifically chose genotypes that did not harbor the facultative endosymbiont Regiella insecticola as previous work has suggested that infection with this bacterium alters wing induction [24]. We also verified that these genotypes did not harbor DplDNV using established PCR protocols [3].…”
Section: Methods Details Variation In Wing Plasticity From a Natural Aphid Populationmentioning
confidence: 99%
“…10 genotypes produced a low percentage of winged-offspring after crowding (weakly inducible genotypes: genotypes 73, 88, 183, 218, 223, 248, 375, 396, 405, & 495), and 10 genotypes produced a high percentage of winged-offspring (highly inducible genotypes: genotypes 42, 125, 179, 202, 217, 281, 286, 445, 473, & 500). We specifically chose genotypes that did not harbor the facultative endosymbiont Regiella insecticola as previous work has suggested that infection with this bacterium alters wing induction [24]. We also verified that these genotypes did not harbor DplDNV using established PCR protocols [3].…”
Section: Methods Details Variation In Wing Plasticity From a Natural Aphid Populationmentioning
confidence: 99%
“…An important role of microbial symbionts for host fitness has been found for a taxonomically diverse group of insects (e.g., Coon, Brown, & Strand, 2016;Reyes et al, 2019;Schwab, Riggs, Newton, & Moczek, 2016). Thus, we tested for associations between abdominal microbial community composition and proxies for colony fitness such as brood quantity and colony size.…”
Section: Abdominal Microbiome Characteristics and Colony Phenotypementioning
confidence: 99%
“…Symbiont infection increases aphid survival and reproduction while decreasing fungal spore production from deceased aphids (27,31,65). R. insecticola has also been associated with changes in the propensity for wing development, possibly with host plant utilization, and with the timing of sexual reproduction in pea aphids (66)(67)(68)(69). Currently, there are no reports that it confers protection against parasitoids in pea aphids (29,35,47).…”
mentioning
confidence: 99%